2012
DOI: 10.1101/gad.193193.112
|View full text |Cite
|
Sign up to set email alerts
|

CDK2-dependent activation of PARP-1 is required for hormonal gene regulation in breast cancer cells

Abstract: Eukaryotic gene regulation implies that transcription factors gain access to genomic information via poorly understood processes involving activation and targeting of kinases, histone-modifying enzymes, and chromatin remodelers to chromatin. Here we report that progestin gene regulation in breast cancer cells requires a rapid and transient increase in poly-(ADP)-ribose (PAR), accompanied by a dramatic decrease of cellular NAD that could have broad implications in cell physiology. This rapid increase in nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 36 publications
6
122
0
Order By: Relevance
“…The assessment of such correlations is further confounded by the fact that the PARP-1 protein can undergo posttranslational modification that impacts on its activity. For instance, it has been recently shown that while PARP-1 enzymatic activity is rapidly enhanced by progestin treatment of breast cancer cells through a mechanism involving the phosphorylation of PARP-1 by CDK2, 32 PARP-1 activity is downregulated after phosphorylation by CDK5. 33 There is very little published information on the expression patterns in breast tumors of the other four transcripts studied here.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…The assessment of such correlations is further confounded by the fact that the PARP-1 protein can undergo posttranslational modification that impacts on its activity. For instance, it has been recently shown that while PARP-1 enzymatic activity is rapidly enhanced by progestin treatment of breast cancer cells through a mechanism involving the phosphorylation of PARP-1 by CDK2, 32 PARP-1 activity is downregulated after phosphorylation by CDK5. 33 There is very little published information on the expression patterns in breast tumors of the other four transcripts studied here.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…To test whether the spatial organization of the genome into TADs is important for the response of T47D breast cancer cells to Pg, we generated Hi-C libraries of cells synchronized in G0/G1 and treated or not with Pg for 60 min, when most of the Pg-induced chromatin modifications that we described previously already occurred (Vicent et al 2008;Wright et al 2012;Ballare et al 2013). In order to minimize artifacts linked to the biased genomic distribution of restriction enzymes (Yaffe and Tanay 2011;Imakaev et al 2012), we generated biological replicates of Pg treatment using, independently, HindIII and NcoI (giving a total of 174,278,292 and 169,171,077 pairs of interacting fragments, respectively, for ÀPg and +Pg cells, respectively) (see the Supplemental Material; Supplemental Table 1).…”
Section: Characterization Of Tads In T47d Cellsmentioning
confidence: 99%
“…We studied the relationship between hormone-regulated changes in transcription, chromatin structure, epigenetic marks, and the 3D structure of TADs. We know that the progestin (Pg)-activated PR cross-talks with kinase signaling networks to modify chromatin and regulate the transcription rate of thousands of target genes by either activation or repression (Migliaccio et al 1998;Vicent et al 2006Vicent et al , 2011Wright et al 2012). Using RNA-seq (RNA sequencing), ChIP-seq (chromatin immunoprecipitation combined with highthroughput sequencing), Hi-C (chromosome capture followed by high-throughput sequencing), and 3D modeling, we confirmed that the T47D genome is organized into ;2000 TADs whose borders are largely stable upon hormone treatment.…”
mentioning
confidence: 99%
“…8 Hormone activated CDK2 also phosphorylates poly (ADP-ribose) polymerase 1 (PARP1), which converts NAD+ to poly(ADP-ribose) (PAR) attached to itself and to linker and core histones, facilitating displacement of histone H1. 9 This initial remodeling step requires also NURF, an ATP-dependent chromatin remodeling complex that is recruited to target sites via interaction with PR and is stabilized by trimethylation of histone H3 at lysine 4 catalyzed by MLL2/3 of the ASCOM complex. 8 In a subsequent remodeling cycle PR recruits the BAF complex that is stabilized by PCAF-mediated acetylation of histone H3 at K14 and catalyzes displacement of histones H2A/H2B dimers ( fig.…”
Section: Pr Binding Sites Are Marked By High Nucleosomes Occupancymentioning
confidence: 99%
“…(B) Upon hormone binding, the activated PR reaches these PREs in association with kinases, histone tails modifiers and NURF that stabilize PR binding via contact with histones and initiate chromatin remodeling (H1 displacement). 8,9 (C) In a subsequent step BAF catalyzes histone H2A/H2B displacement. 10 (D) After chromatin remodeling, PR interacts with other TFs, co-regulators and components of the transcriptional machinery, to promote formation of the transcription initiation complex.…”
Section: Pr Binding Sites Are Marked By High Nucleosomes Occupancymentioning
confidence: 99%